THE ROLE OF GREATER AMMAN MUNICIPALITY IN THE MAKING OF A KNOWLEDGE CITY - Shaqrah, Amin (European Scientific Journal, ESJ, 2014)
This study investigates the role Greater Amman Municipality “GAM” in the making of a successful knowledge city. Researcher determined the role through activities include: productivity and competiveness, business and enterprises, knowledge and technology, skills and learning, key centers, participants and leadership. To address these activities, a semi-structured interviews and conversations were concerned about raising the crucial issues to have knowledge city in Amman. The results concluded that all above activities applied on GAM and facilitate transform Amman to a knowledge city. It also illustrates how the GAM play a key role in developing Amman as a globally recognized, entrepreneurial and competitive knowledge city.